What slows the progress of health systems strengthening at subnational level? A political economy analysis of three districts in Uganda. - Justine Namakula; Xavier Nsabagasani; Ligia Paina; Abigail Neel; Chimwemwe Msukwa; Daniela C Rodriguez; Freddie Ssengooba (PLOS Global Public Health)
There is increasing recognition that without stronger health systems, efforts to improve global health and Universal Health Coverage cannot be achieved. Over the last three decades, initiatives to strengthen health systems in low-income countries have attracted huge investments in the context of achieving the Millennium Development Goals, the Sustainable Development Goals, as well as Universal Health Coverage. Yet, health system inadequacies persist, especially at the subnational level. Our paper presents a political economy analysis featuring a three-district case study in Uganda, where district-based health systems strengthening initiatives were implemented. The study sought to understand why health systems at the subnational level are failing to improve despite marked investments. This problem-based political economy analysis draws from a document review and key informant interviews [N = 49] at the central and district levels with government actors, development partners, and civil society in three purposively selected districts. Available financial data extraction and analysis were used to complement qualitative data. We found that challenges in strengthening district health systems were numerous. Themes related to financing and planning broadly interacted to curtail progress on strengthening subnational-level health systems. Specific challenges included inadequate financing, mismatch of resources and targets, convoluted financial flows, as well as unwieldy bureaucratic processes. Sticky issues related to the planning process included variations in planning cycles, conflicting interests among actors, insufficient community engagement, limited decision space, and distorted accounting mechanisms. In conclusion, the political economy analysis lens was a useful tool that enabled an understanding of the dynamics of decision-making and resource allocation within district health systems, as well as the performance in terms of implementation of the district work and plans with existing resources. Whereas the district health teams play a big role in service program implementation, the context in which they work needs to be improved in terms of sufficient resources, setting realistic targets, widening the decision space and capacity necessary to engage with other various stakeholders and effectively harmonize the implementation of the programs. Despite playing a crucial role in compensating for local shortfalls in resources, donor resources and engagements should not happen at the cost of the subnational voice in priority setting and decision-making.